Hybrid bilevel optimization-based interaction between the distribution grid and PV microgrids with differentiated demand response - Shao, Zhimin; Liu, Chunxiu; Yao, Rui; Wang, Cong; Li, Longtan; Liu, Zhen; Liu, Yimin; Zhou, Zaiyan (Frontiers in Energy Research, 2023)
Demand response plays an important role in improving the balance of power generation and consumption between distribution grid and photovoltaic (PV) microgrids. However, due to the uncertainty and volatility of PV output, as well as the different operation goals of PV microgrids, conventional single-tier optimization approach is infeasible to realize the coordinated interaction between distribution grid and PV microgrids. To address these challenges, we propose a secondorder cone and improved consensus algorithm-based hybrid bilevel optimization algorithm for the interaction between distribution grid and PV microgrids. First, we construct price-based and incentive-based differentiated demand response models to deal with various supply and demand dynamics of distribution grid and PV microgrids. Building upon this foundation, we construct a hybrid bilevel optimization model. In the lower level, distributed optimization is adopted, and an improved consensus algorithm is used to optimize power output of PV microgrids to maximize the revenue based on output power of upper-level generator sets. In the upper level, centralized optimization is adopted, and the second-order cone programming is employed to minimize the grid loss in the distribution grid based on the power output of lower-level PV microgrids. The hybrid bilevel optimization is iterated until the convergence condition is satisfied. Simulation results verify the proposed algorithm for achieving coordinated interaction between distribution grid and PV microgrids.